SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN DAGING KAMBING BERKUALITAS BAIK DENGAN METODE FUZZY SUGENO BERBASIS ANDROID - Achmad Dika Asrori; Retno Wardhani; Masruroh Masruroh (Jurnal Teknika, 2018)
The decision support system used to determine good quality meat using Fuzzy Sugeno Method is made using Eclipse Application with some stages, those are: making the project then create the layout file and Java, after that design stage and coding are done once the project is ready to run. The results of the calculation on the Fuzzy Sugeno Method test show that there are five variables. First, the color of meat has three sets. It is categorized as bad 1 if it is in the range of 1-3,  good in the range of 4-6, and bad 2 in the range of 7-8. The second variable is related to the fat color. It has two sets, those are bad if it is in the range of 4-9 and good in the range 1-3. The third variable is marbling which has two sets, those are bad if it is in the range of 1-9 and good in the range of 10-12. The fourth variable has three sets, those are bad 1 if it is in the range of 0-4, good in the range of 5,3-5,8, and bad 2 in the range of 5,8-8 . The third category of marbling has two sets, those are bad if it is in the range of 8 and good in the range of 8.